DomesticBeethoven/bith-annotator: Release 2023-04 - Kepper, Johannes
This release covers the state of this prototype app at the end of the funding phase for the Paderborn University part of the Beethoven in the House project. It uses https://api.domestic-beethoven.eu/ld/BithCollection.jsonld as starting point for traversing the LOD graph, and reads data from the project pod available from https://bith.solidcommunity.net/public/bith.ttl (which has no content at the time of the release).
Keywords: MEI; Edirom; Music Encoding Initiative; Linked Open Data; MELD

MEI: The Music Encoding Initiative Guidelines (PDF)
PDF versions of the Music Encoding Initiative Guidelines 5.0 [2023]: This version represents the 5.0 release of the Music Encoding Initiative Guidelines.

Beethoven in the House: Selective Encodings of Arrangements of Beethoven’s opp. 91, 92, and 93. - Rosendahl, Lisa
This dataset contains selective MEI encodings of a number of arrangements of Beethoven’s Opp. 91, 92, and 93. These encodings were prepared in the context of the Beethoven in the House project, jointly funded by AHRC and DFG from 2020 to 2023. It is a slight update on v1.0.0 in better organizing the release assets.
Keywords: BitH; Dataset; Domestic Music Arrangements; Ludwig van Beethoven; MEI; Music Encoding Initiative

A New Conceptual Model for Musical Sources and Musicological Studies - Shibata, Elisabete; Lewis, David; Saccomano, Mark; Kepper, Johannes; Page, Kevin (Proceedings of the Music Encoding Conference 2022)
We present a new multi-layered, conceptual model for associating musical source materials to musicological arguments. We describe our proposal for operationalizing these concepts through a framework for musical annotation which we have implemented using RDF. Briefly stated, this model shows how portions of digitized data in various files and formats can be identified, selected, labelled, and compared.
Keywords: BitH; Linked Data

Supporting Musicological Investigations With Information Retrieval Tools: An Iterative Approach to Data Collection - Lewis, David; Shibata, Elisabete; Hankinson, Andrew; Kepper, Johannes; Page, Kevin R.; Rosendahl, Lisa; Saccomano, Mark; Siegert, Christine
Digital musicology research often proceeds by extending and enriching its evidence base as it progresses, rather than starting with a complete corpus of data and metadata, as a consequence of an emergent research need. In this paper, we consider a research workflow which assumes an incremental approach to data gathering and annotation. We describe tooling which implements parts of this workflow, developed to support the study of nineteenth-century music arrangements, and evaluate the applicability of our approach through interviews with musicologists and music editors who have used the tools. We conclude by considering extensions of this approach and the wider implications for digital musicology and music information retrieval.
Keywords: BitH; Linked Data

Temporal Sorting of Optical Multiwave-Mixing Processes in Semiconductor Quantum Dots - Grisard, Stefan; Trifonov, Artur V.; Rose, Hendrik; Reichhardt, Rilana; Reichelt, Matthias; Schneider, Christian; Kamp, Martin; Höfling, Sven; Bayer, Manfred; Meier, Torsten; Akimov, Ilya A. (ACS Photonics)

Review of: Open Citizen Science: fostering open knowledge with participation. - Mauermeister, Sylvi (Research Ideas and Outcomes)

Expertise and professionalism for inclusive (mathematics) teaching and learning: reflections on findings from interdisciplinary professionalisation research - Seitz, Simone; Häsel-Weide, Uta; Wilke, Yannik; Wallner, Melina (Teachers and Teaching)
Keywords: Arts and Humanities (miscellaneous); Education

Methodenentwicklung zur Verbesserung der Schädigungsmodellierung in der numerischen 3D-Belastungssimulation mechanischer Fügeverfahren unter Berücksichtigung der fügeinduzierten Vorbeanspruchung - Rossel, Moritz Sebastian; Meschut, Gerson; Bielak, Christian Roman; Otroshi, Mortaza

Geschichte der italienischen Zuwanderung nach Belgien im Medium Comic: Macaroni! (2016) und Une histoire importante. 70 ans d’immigration italienne en Belgique et plus (2019) - Schmitz, Sabine (Letteratura e migrazione/Literatur und Migration. Proposte intorno alla figura del ponte/ Fragen zur Figur der Brücke)

Lo fantástico en la escena del crimen: análisis del proceso de adaptación de la historieta El hipnotizador (2007) de Pablo de Santis y Juan Sáenz Valiente a la serie televisiva homónima de HBO Latin América (2015) - Schmitz, Sabine (Inter/Transmedialidad en el género negro y policial latinoamericano)

Phantastik in Belgien: Erzählungen von Franz Hellens und Thomas Gunzig über Doppelgänger, Monster und Kuhfräulein - Schmitz, Sabine; Schädlich, Birgit (Belgien – anregend anders. Fachwissenschaft und Fachdidaktik untersuchen die Vielfalt der Sprachen, Literaturen und Kulturen in Belgien)

Brückenbau oder Steg der Erinnerung? Narrationen zur italienischen Arbeitsmigration des 20. Jahrhunderts im aktuellen belgischen Comic - Schmitz, Sabine (Letteratura come ponte? Littérature comme pont? Literatur als Brücke? Zur Frage von Migration und Literatur)

Prólogo - Schmitz, Sabine; Verdú Schumann, Daniel (Inter/Transmedialidad en el género negro y policial latinoamericano)

Belgien – anregend anders. Fachwissenschaft und Fachdidaktik untersuchen die Vielfalt der Sprachen, Literaturen und Kulturen in Belgien

Inter/Transmedialidad en el género negro y policial latinoamericano

Digitale Desökonomie: Unproduktivität, Trägheit und Exzess im digitalen Milieu - Althoff, Sebastian
Die Warnung von Eltern, aufzupassen, was man online teilt, ist allgegenwärtig. Dem schließen sich Datenschützer*innen an und gebieten einen bewussten und sparsamen Umgang mit Diensten und Daten. Eine digitale Desökonomie widersetzt sich diesen Warnungen und sucht den kritischen Umgang mit der digitalen Gegenwartskultur nicht in der Askese, sondern im Exzess. Kunstwerke, Bilder und Daten sind »zu viel«, türmen sich auf und wiederholen sich ständig. Mit Bezug auf Ansätze der Gouvernementalität, der Queer Theory und auf Theorien von Georges Bataille und Roger Caillois analysiert Sebastian Althoff diese unproduktive Produktionsweise des Digitalen und zeigt eine Praxis auf, die Trägheit statt flow schafft.

Janus-type emission from a cyclometalated iron(iii) complex - Steube, Jakob; Kruse, Ayla; Bokareva, Olga S.; Reuter, Thomas; Demeshko, Serhiy; Schoch, Roland; Argüello Cordero, Miguel A.; Krishna, Athul; Hohloch, Stephan; Meyer, Franc; Heinze, Katja; Kühn, Oliver; et al. (Nature Chemistry)
Abstract Although iron is a dream candidate to substitute noble metals in photoactive complexes, realization of emissive and photoactive iron compounds is demanding due to the fast deactivation of their charge-transfer states. Emissive iron compounds are scarce and dual emission has not been observed before. Here we report the Fe III complex [Fe(ImP) 2 ][PF 6 ] (HImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazol-2-ylidene)), showing a Janus-type dual emission from ligand-to-metal charge transfer (LMCT)- and metal-to-ligand charge transfer (MLCT)-dominated states. This behaviour is achieved by a ligand design that combines four N -heterocyclic carbenes with two cyclometalating aryl units. The low-lying π * levels of the cyclometalating units lead to energetically accessible MLCT states that cannot evolve into LMCT states. With a lifetime of 4.6 ns, the strongly reducing and oxidizing MLCT-dominated state can initiate electron transfer reactions, which could constitute a basis for future applications of iron in photoredox catalysis.
Keywords: General Chemical Engineering; General Chemistry

Was heißt Überleben? Die Zweischneidigkeit eines ubiquitären Begriffs - Althoff, Sebastian (Berliner Debatte Initial)
Der Begriff des Überlebens vereinigt in sich ganz unterschiedliche Vorstellungen, die ganz unterschiedlichen Politiken Vorschub leisten: In Überlebensratgebern, -sendungen und -filmen findet das Überleben fernab der Zivilisation statt, in der Wildnis oder nach einer Katastrophe. Überleben bedeutet dabei die Fortsetzung des nackten Lebens. In den Schriften Schwarzer, feministischer und queerer Autor*innen findet das Überleben dagegen im Hier und Jetzt statt, ist eine Konsequenz staatlicher, ‚zivilisierter‘ Ordnung und beinhaltet mehr als das nackte Leben, beinhaltet etwa Gemeinschaft und den Ausdruck von Identität. Der Artikel skizziert die unterschiedlichen politischen Konsequenzen, die aus diesen Verständnissen erwachsen, die konservierend und reproduktiv oder transformativ wirken können, die Dinge als existentiell oder veräußerbar beschreiben, die den Status Quo erhalten oder Veränderungen einfordern können.

Responses to heat waves: what can Twitter data tell us? - Zander, Kerstin K.; Rieskamp, Jonas; Mirbabaie, Milad; Alazab, Mamoun; Nguyen, Duy (Natural Hazards)
Abstract Increasing average temperatures and heat waves are having devasting impacts on human health and well-being but studies of heat impacts and how people adapt are rare and often confined to specific locations. In this study, we explore how analysis of conversations on social media can be used to understand how people feel about heat waves and how they respond. We collected global Twitter data over four months (from January to April 2022) using predefined hashtags about heat waves. Topic modelling identified five topics. The largest (one-third of all tweets) was related to sports events. The remaining two-thirds could be allocated to four topics connected to communication about climate-related heat or heat waves. Two of these were on the impacts of heat and heat waves (health impacts 20%; social impacts 16%), one was on extreme weather and climate change attribution (17%) and the last one was on perceptions and warning (13%). The number of tweets in each week corresponded well with major heat wave occurrences in Argentina, Australia, the USA and South Asia (India and Pakistan), indicating that people posting tweets were aware of the threat from heat and its impacts on the society. Among the words frequently used within the topic ‘Social impacts’ were ‘air-conditioning’ and ‘electricity’, suggesting links between coping strategies and financial pressure. Apart from analysing the content of tweets, new insights were also obtained from analysing how people engaged with Twitter tweets about heat or heat waves. We found that tweets posted early, and which were then shared by other influential Twitter users, were among the most popular. Finally, we found that the most popular tweets belonged to individual scientists or respected news outlets, with no evidence that misinformation about climate change-related heat is widespread.
Keywords: Earth and Planetary Sciences (miscellaneous); Atmospheric Science; Water Science and Technology